Beberapa faktor yang berhubungan dengan keputusan Pembelian Susu Formula - Mardiana Mardiana; Nindia Ayu Pangesti; Yulianto Yulianto; Podojoyo Podojoyo; Eliza Eliza (JGK:Jurnal Gizi dan Kesehatan, 2023)
ABSTRACT Background The purchase decision is one of the indications that indicates whether or not a product is accepted by consumers. Location determination based on data on the highest number of cases of malnutrition status (BB/U) in Palembang City, namely in the working area of the Nagaswidak Health Center with 370 cases.Objective: To determine the relationship between the price, nutritional knowledge, income level and advertising of milk with the decision to buy formula milk. Method: The study design was in the form of quantitative crosssectional with a sample of 32 mothers who had toddlers aged between 1 to 3 years using Lemeshow calculations plus a 10% reserve selected using purposive sampling techniques. Data collection on formula milk purchasing decisions, prices, nutritional knowledge, income levels, and direct milk advertising is using questionnaires, observations and by taking anthropometric measurements. The data were analyzed univariately and bivariately using the Chi-Square test. Results: The results showed that there was a relationship between price (p<0.001) and income level (p = 0.03) with purchasing decisions and there was no relationship between nutritional knowledge (p = 0.357) and milk advertising (p = 0.169) with consumer decisions.Conclusion: It was concluded that the price of milk and the income of a person contain a positive relationship with the decision to purchase milk and the level of knowledge of the mother is quite an important factor towards the decision to purchase a food.